Examining The Relationship Between Customer Experience and Brand Image: Case Studies At German Dealerships - Vasantha Rao, Taidala; Babu Vemula, Prasanth; Nadikuditi, Lavanya (International Journal of Psychosocial Rehabilitation, 2019)
There has been an increase of attention on the term customer experience and it became a buzzword in marketing. However, marketing science has been slow in developing new literature insights on customer experience. To address this gap, this paper explores how car companies are successfully establishing their brands with the help of customer experience management techniques. A series of case studies examining three German luxury car brands - namely Mercedes, BMW and Audi - has been conducted in a rural to midsized urban setting in West-Germany. The studies include the analysis of customers, employees and physical elements of the dealerships. Main findings include that dealerships who provide vehicles in rural to midsized populated areas have challenges to attract customers because of their remote locations. Practises that offer experience to customers are promotions and events. Overall, there is plenty of experience offered, not only the cars provide experience but also the service offerings like inspections or a friendly but professional atmosphere provided by the sales people. The dealerships itself are having smart designs and layouts that help amplifying the customer experience. All these measurements can help establish and facilitate brand images that is set by the extensive histories of the brands.